General Helices of AW(k)-Type in the Lie Group - Dae Won Yoon (Journal of Applied Mathematics)
We study curves of AW(k)-type in the Lie group G with a bi-invariant metric. Also, we characterize general helices in terms of AW(k)-type curve in the Lie group G.